Effectiveness of intralesional vitamin D3 injections for treatment of common warts: An open-label uncontrolled study - Naseer , Maria; Tanveer, Nida; Mughal, Ramla; Maheshwary, Neeta (Journal of Pakistan Association of Dermatologists, 2023)
Objective: To evaluate the effectiveness of intralesional Vitamin D3 in the treatment of common warts. Study Design: Open-label uncontrolled, single blind, and single centre experimental study Place and Duration of Study: JPMC Karachi City between August 9, 2019 to October 8, 2022 Â Methodology: To be eligible for the study, participants had to have common warts and must not have undergone any topical or destructive treatments for a minimum of six months. The study included both males and females between the ages of 12 and 60. The procedure involved injecting lignocaine (20 mg/ml) into the warts using a 27-gauge insulin syringe and aseptic methods, followed by injecting 0.5 ml of vitamin D3 (15 mg/ml) into the base of each wart. The reduction in the number and size of warty lesions was monitored during each visit, which occurred every two weeks for a total of four sessions. Results:Â A total of 356 patients were enrolled in the study and were assigned to receiving injections of vitamin D3. Three hundred forty five patients completed the study. Out of the total number of individuals who received the intervention (n=345), 211 (61.2%) showed a complete clearance response, 97 (28.1%) showed a moderate response, and 21 (6.1%) showed a mild response. Conclusion: Overall, these studies suggest that intralesional vitamin D3 injections are effective in the treatment of common warts. Â Â Â Â